Digital Journeys: A Perspective on Understanding the Digital Experiences of International Students - Chang, Shanton; Gomes, Catherine (Journal of International Students, 2017)
The authors in this conceptual paper draw on the literature on information seeking behavior, social media use, and international student experiences to propose Digital Journeys as a framework which helps us understand the online behavior of international students. Here we theorize that the Digital Journey is the transition that individuals make online from relying on one digital bundle of information sources to a new bundle. This “new” digital bundle possibly can base in the new host country or internationally. We furthermore suggest that Digital Journeys is not only an under investigated phenomenon but a thoroughly necessary space to examine in order to improve the ways in which we present information to international students.